A method for preparing high-strength self-repairing gel elastomer
By using the esterification reaction of monomers such as MEA, NIPAM, AA and para-hydroxybenzaldehyde and crosslinking of polyetheramines in polymer materials, a high-strength self-healing gel elastomer was constructed, solving the mechanical properties and self-healing. The balance between performance has achieved efficient self-repair and mechanical performance improvement.
Patent Information
- Application Number
- CN202211221578.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-10-08
AI Technical Summary
It is difficult to achieve a balance between improving mechanical properties and self-repairing properties, resulting in the material being prone to fracture when stress overloaded and the self-repairing efficiency is low.
The esterification reaction is carried out using monomers such as MEA, NIPAM, AA and parahydroxybenzaldehyde to form a terpolymer, and the crosslinking of polyetheramines forms a reversible imine crosslink to construct a high-strength self-healing gel elastomer. , improve mechanical performance and self-repair efficiency.
It achieves significant improvement in self-repair efficiency while ensuring mechanical properties, forming a non-dissolved mesh polymer structure, enhancing the mechanical properties and self-repair performance of the material, and is suitable for a variety of application environments.
Smart Images

Figure CN115418010B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of self-repairing materials, and in particular to a method for preparing a high-strength self-repairing gel elastomer. Background Art
[0002] Self-healing materials are usually flexible and stretchable, and their self-healing properties give them excellent fatigue resistance. Even in extreme cases of damage and fracture, they can still restore a certain mechanical strength through self-healing functions.
[0003] Generally speaking, there is a contradictory relationship between self-repair efficiency and mechanical properties. The tensile fracture of polymer materials is mainly caused by the following two reasons: the first is that the strength of the polymer chain itself is insufficient, and the molecular chain breaks under stress overload; the second is that the interaction between polymer chains is not strong, and the chain slippage causes fracture under stress. Therefore, high strength needs to start from two aspects: improving the strength of the molecular chain and increasing the interaction between molecular chains. In essence, it requires the entire polymer system to remain as static as possible. Self-repair is just the opposite. The realization of self-repair requires the exchange, penetration or reaction of substances between interfaces to achieve fusion between cross-sections and reconstruction of forces. In essence, it requires the system to be a dynamic effect. Therefore, the construction of high-strength self-repairing materials is to seek a balance between the two, but the achievement of this balance still faces great difficulties and is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a high-strength self-repairing gel elastomer.
[0005] The technical solution of the present invention to solve the technical problem is to provide a method for preparing a high-strength self-repairing gel elastomer, characterized in that the method comprises the following steps:
[0006] Step 1, dissolving MEA, NIPAM, AA and initiator in a sufficient or excessive amount of solvent, and then polymerizing in a sealed oxygen-free environment for 8 to 16 hours; then cooling the temperature to stop the polymerization reaction, so that the active intermediate becomes a stable compound, and a viscous copolymer liquid is obtained; then the viscous copolymer liquid is extracted with an ether liquid to remove unreacted small molecules, and then the extracted product is placed in a purification agent for dialysis purification to remove the solvent and the ether liquid, and after drying to remove the purification agent, a terpolymer is obtained;
[0007] Step 2, dissolving the terpolymer in a sufficient or excessive amount of solvent to form a homogeneous system; then adding p-hydroxybenzaldehyde, DMAP and DCC, and performing an esterification reaction at room temperature for 20 to 28 hours; then centrifuging the solution after the reaction; placing the separated supernatant in a dialysis bag, and then placing the dialysis bag in a purifying agent for dialysis purification to remove unreacted small molecules and solvents, and drying to remove the purifying agent to obtain an aldehyde-modified copolymer;
[0008] Step 3, stirring and dissolving the aldehyde-modified copolymer in a sufficient or excessive amount of solvent to obtain a aldehyde-modified copolymer solution; dissolving the polyetheramine in the solvent as a cross-linking stock solution; then stirring the cross-linking stock solution and the aldehyde-modified copolymer solution at room temperature until they are uniformly mixed, vacuum degassing, placing at a temperature of 30 to 50° C. for cross-linking and gelation, and drying to remove the solvent to obtain a gel elastomer.
[0009] Compared with the prior art, the present invention has the following beneficial effects:
[0010] (1) The present invention first introduces acrylic acid monomers as grafting sites, constructs MEA, NIPAM and AA into a ternary copolymer, and then undergoes an esterification reaction with p-hydroxybenzaldehyde to convert it into an aromatic aldehyde cross-linking site. Finally, a reversible imine cross-linking is formed by a Schiff base reaction with a low-activity polyether amine to form a gel elastomer, which greatly improves the self-healing efficiency while ensuring the mechanical properties.
[0011] (2) The present invention simply and effectively constructs a high-strength self-healing gel elastomer driven by chain motion and reconstructing the van der Waals forces and hydrogen bonds between cross sections by solubilizing and copolymerizing the low-Tg MEA soft segment monomer and the temperature-sensitive NIPAM hard segment monomer. The superposition of forces at multiple sites significantly improves the mechanical properties of the material.
[0012] (3) The gel elastomer prepared by the present invention has excellent mechanical properties and self-healing properties. Through cross-linking, the molecular chain is transformed from linear to network. When placed in solvents such as water, anhydrous ethanol, DMSO, DMF, acetone, and dichloromethane, the polymer chain cannot move freely (i.e., dissolve), but can only fill the network (i.e., swell), indicating that the gel elastomer is not easily soluble and can be used in more application environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The FTIR spectrum and a partial enlarged view of the FTIR spectrum of the terpolymer, the aldehyde-modified copolymer and the gel elastomer of Example 3 of the present invention;
[0014] Figure 2 TG spectra of the terpolymer, the aldehyde-modified copolymer and the gel elastomer of Example 3 of the present invention, the gel elastomer of Example 1 and the gel elastomer of Example 2;
[0015] Figure 3 The DSC spectra of the terpolymer, the aldehyde-modified copolymer and the gel elastomer of Example 3 of the present invention, the gel elastomer of Example 1 and the gel elastomer of Example 2;
[0016] Figure 4 This is an AFM morphology image of the product of Comparative Example 1 of the present invention;
[0017] Figure 5 This is an AFM morphology image of the terpolymer of Example 3 of the present invention;
[0018] Figure 6 This is an AFM morphology image of the gel elastomer of Example 3 of the present invention;
[0019] Figure 7 The stress-strain diagrams are the product of Comparative Example 1 of the present invention, the terpolymer, the aldehyde-modified copolymer and the gel elastomer of Example 3, the gel elastomer of Example 1 and the gel elastomer of Example 2;
[0020] Figure 8 This is a graph of the terpolymer of Example 3 of the present invention subjected to 5 consecutive cycles of stretching with a strain of 300%;
[0021] Fig. 9 The gel elastomer of Example 3 of the present invention is subjected to cyclic stretching for 5 consecutive times with a strain of 300%;
[0022] Fig.10 The optical microscopic observation graphs of the scratch repair of the gel elastomer of Example 3 of the present invention at room temperature and 75° C. at different times;
[0023] Fig.11 The self-repairing tensile diagram of the gel elastomer of Example 3 of the present invention after 12 hours at different temperatures;
[0024] Fig.12 The self-repairing tensile diagram of the gel elastomer of Example 1 of the present invention at 100° C. at different times;
[0025] Fig.13 The self-repairing tensile diagram of the gel elastomer of Example 2 of the present invention at 100° C. at different times;
[0026] Fig.14 It is the self-healing stretching diagram of the gel elastomer of Example 3 of the present invention at 100°C for different time periods. DETAILED DESCRIPTION
[0027] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the claims of the present invention.
[0028] The present invention provides a method for preparing a high-strength self-repairing gel elastomer (hereinafter referred to as the method), characterized in that the method comprises the following steps:
[0029] Step 1, dissolving MEA (2-methoxyethyl acrylate), NIPAM (N-isopropylacrylamide), AA (acrylic acid) and an initiator in a sufficient or excessive amount of solvent, and then heating and stirring in a sealed oxygen-free environment to carry out a polymerization reaction for 8 to 16 hours; then cooling the polymerization reaction to stop the polymerization reaction, so that the active intermediate becomes a stable compound, and a viscous copolymer liquid is obtained; then the viscous copolymer liquid is extracted with an ether liquid to remove unreacted small molecules, and then the extracted product is placed in a purification agent for dialysis purification to remove the solvent and the ether liquid, and after drying to remove the purification agent, a terpolymer is obtained;
[0030] Preferably, in step 1, the molar ratio of MEA, NIPAM, AA and initiator is (40-95):(5-60):(1-10):(1-5).
[0031] Preferably, in step 1, the initiator is one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, benzoyl peroxide, potassium persulfate, ammonium persulfate or sodium persulfate; and the reaction temperature of the polymerization reaction is 60 to 90°C.
[0032] Preferably, in step 1, the sealed oxygen-free environment is: bubbling with an inert gas for 5 to 30 minutes to completely eliminate oxygen in the reaction environment and the reaction system, and then sealing the reaction container (a flask in this embodiment) by a rubber diaphragm; the inert gas is nitrogen or argon.
[0033] Preferably, in step 1, the cooling operation can be performed by quenching in an ice bath to stop the polymerization reaction and achieve rapid cooling, so that the molecular weight of the products tends to be the same and the molecular weight distribution is uniform.
[0034] Preferably, in step 1, the extraction is carried out in a small amount and multiple times, and the number of extractions is 2 to 5 times; the specific process of each extraction is: firstly, the ether liquid and the viscous copolymer liquid are mixed evenly by shaking, and then the stratification is accelerated by centrifugation; the ether liquid is methyl tert-butyl ether.
[0035] Preferably, the dialysis purification time is 18 to 30 hours, and the purification agent is replaced every 6 to 8 hours; the purification agent is deionized water.
[0036] Preferably, in step 1, the drying temperature is 50-100°C.
[0037] Step 2, stirring and dissolving the terpolymer obtained in step 1 in a sufficient or excessive amount of solvent to form a homogeneous system; then adding p-hydroxybenzaldehyde, DMAP (4-dimethylaminopyridine) and DCC (N,N"-dicyclohexylcarbodiimide) to carry out esterification reaction at room temperature for 20 to 28 hours; then centrifuging the solution after the reaction; placing the separated supernatant in a dialysis bag, and then placing the dialysis bag in a purifying agent for dialysis purification to remove unreacted small molecules and solvents, and drying to remove the purifying agent to obtain an aldehyde-modified copolymer;
[0038] Preferably, in step 2, the mass ratio of the terpolymer, p-hydroxybenzaldehyde, DMAP and DCC is (400-500):(20-40):(2-4):(45-60).
[0039] Preferably, in step 2, during the esterification reaction, DCC is dehydrated and esterified to form insoluble solid DCU (dicyclohexylurea), and the solution gradually changes from an orange clear solution to a turbid solution. The esterification reaction is preferably carried out under stirring.
[0040] Preferably, in step 2, the concentration of the terpolymer in the homogeneous system is 200-300 mg / mL; the dialysis purification time is 18-30 hours, and the purification agent is replaced every 6-10 hours; and the purification agent is deionized water.
[0041] Preferably, in step 2, the molecular weight cutoff of the dialysis bag ensures that the reaction product cannot enter or exit the dialysis bag, while the solvent and the purification agent can enter or exit the dialysis bag; the molecular weight cutoff of the dialysis bag is preferably 3000 to 20000.
[0042] Preferably, in step 2, the drying can be performed by vacuum drying at a temperature of 40 to 50° C. for 36 to 60 hours.
[0043] Step 3, stirring and dissolving the aldehyde-modified copolymer obtained in step 2 in a sufficient or excessive amount of solvent to obtain a homogeneous, clear and viscous aldehyde-modified copolymer solution;
[0044] Dissolving polyetheramine (preferably polyetheramine D-400) in a solvent (preferably the same solvent as that for dissolving the aldehyde-modified copolymer) as a cross-linking stock solution;
[0045] At room temperature, the cross-linking stock solution and the aldehyde copolymer solution are stirred until they are uniformly mixed. After vacuum degassing, they are placed at a temperature of 30 to 50° C. for cross-linking and gelation, and dried to remove the solvent, thereby obtaining an imine-crosslinked copolymer with controllable cross-linking density, namely a gel elastomer.
[0046] Preferably, in step 3, after the aldehyde-modified copolymer is dissolved, vacuum filtration is performed to remove solid impurities.
[0047] Preferably, in step 3, the mass ratio of the solvent in the aldehyde copolymer solution to the solvent in the cross-linking stock solution is 300 to 500:1.
[0048] Preferably, in step 3, the stirring time of the cross-linking stock solution and the aldehyde copolymer solution is 5 to 20 minutes.
[0049] Preferably, in step 3, the time for cross-linking, gelation and drying is 3 to 10 hours, depending on the drying state of the product.
[0050] Preferably, in step 3, the crosslinking density is 0.01 to 0.3 mol% (molar percentage). The amount of the polyetheramine is calculated according to the content of p-hydroxybenzaldehyde used in preparing the aldehyde-modified copolymer in step 2 and the crosslinking density, that is, the crosslinking density is adjusted by controlling the content of p-hydroxybenzaldehyde and the content of the polyetheramine. Crosslinking density = molar mass of the reacted aldehyde group / molar mass of the total aldehyde group = molar mass of the amino group / molar mass of the total aldehyde group = 0.5×molar mass of the polyetheramine / molar mass of p-hydroxybenzaldehyde.
[0051] Preferably, in steps 1 to 3, the solvent is one of anhydrous ethanol, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), acetone or dichloromethane, preferably DMSO in step 1, preferably DMF in step 2, and preferably anhydrous ethanol in step 3.
[0052] Example 1
[0053] (1) 7.2 mL of MEA, 2.77 g of NIPAM, 50 μL of AA and 40 mg of AIBN were dissolved in 32 mL of DMSO, and then nitrogen was bubbled for 10 min to completely eliminate oxygen in the reaction environment and the reaction system. The reaction vessel was then sealed with a rubber diaphragm, and polymerized under magnetic stirring at 70° C. for 12 h, and then quenched in an ice bath to obtain a viscous copolymer liquid; the viscous copolymer liquid was then extracted three times with methyl tert-butyl ether, and the extracted product was placed in deionized water for dialyzed purification, and finally dried in a drying oven at 80° C. to obtain a terpolymer;
[0054] (2) Dissolve 5 g of the terpolymer in 20 mL of DMF and stir until completely dissolved to form a homogeneous system; then add 307.5 mg of p-hydroxybenzaldehyde, 31 mg of DMAP and 522 mg of DCC, and stir for esterification reaction at room temperature for 24 h; then centrifuge the solution after the reaction; pour the separated supernatant into a dialysis bag with a molecular weight cutoff of 3000, and then place the dialysis bag in deionized water for 24 h, replace the deionized water every 8 h, and then dry under vacuum at 50° C. for 48 h to obtain the aldehyde-modified copolymer;
[0055] (3) dissolving 5 g of the aldehyde-modified copolymer in 20 mL of anhydrous ethanol, and after the copolymer is completely dissolved, vacuum filtration is performed to remove trace amounts of DCU crystals and other solid impurities to obtain a aldehyde-modified copolymer solution;
[0056] The calculated polyetheramine D-400 was dissolved in 500 μL of anhydrous ethanol as the cross-linking stock solution;
[0057] Then, at room temperature, the cross-linking stock solution and the aldehyde copolymer solution were stirred for 10 minutes until they were evenly mixed, and then poured into a tetrafluoroethylene mold for vacuum degassing, placed at a temperature of 50°C for cross-linking and gelation, and dried to remove the solvent to obtain a gel elastomer, wherein the cross-linking density was controlled to be 0.04 mol%.
[0058] After testing, the maximum stress of the gel elastomer is 3.4MPa and the maximum strain is 650%.
[0059] Example 2
[0060] (1) Same as step (1) of Example 1;
[0061] (2) Same as step (2) of Example 1;
[0062] (3) dissolving 5 g of the aldehyde-modified copolymer in 20 mL of anhydrous ethanol, and after the copolymer is completely dissolved, vacuum filtration is performed to remove trace amounts of DCU crystals and other solid impurities to obtain a aldehyde-modified copolymer solution;
[0063] The calculated polyetheramine D-400 was dissolved in 500 μL of anhydrous ethanol as the cross-linking stock solution;
[0064] Then, at room temperature, the cross-linking stock solution and the aldehyde copolymer solution were stirred for 10 minutes until they were evenly mixed, and then poured into a tetrafluoroethylene mold for vacuum degassing, placed at a temperature of 50°C for cross-linking and gelation, and dried to remove the solvent to obtain a gel elastomer, wherein the cross-linking density was controlled to be 0.08 mol%.
[0065] After testing, the maximum stress of the gel elastomer is 3.2MPa and the maximum strain is 550%.
[0066] Example 3
[0067] (1) Same as step (1) of Example 1;
[0068] (2) Same as step (2) of Example 1;
[0069] (3) dissolving 5 g of the aldehyde-modified copolymer in 20 mL of anhydrous ethanol, and after the copolymer is completely dissolved, vacuum filtration is performed to remove trace amounts of DCU crystals and other solid impurities to obtain a aldehyde-modified copolymer solution;
[0070] The calculated polyetheramine D-400 was dissolved in 500 μL of anhydrous ethanol as the cross-linking stock solution;
[0071] Then, at room temperature, the cross-linking stock solution and the aldehyde copolymer solution were stirred for 10 minutes until they were evenly mixed, and then poured into a tetrafluoroethylene mold for vacuum degassing, placed at a temperature of 50°C for cross-linking and gelation, and dried to remove the solvent to obtain a gel elastomer, wherein the cross-linking density was controlled to be 0.12 mol%.
[0072] After testing, the maximum stress of the gel elastomer is 2.98MPa and the maximum strain is 510%.
[0073] Depend on Figure 1 It can be seen that the amount of acrylic acid added is only 5%, and the characteristic peak of its carboxylic acid is very repetitive with other groups in the terpolymer and is therefore masked. After the terpolymer is aldehyde-formulated by esterification, the generated ester bond is repeated with the ester bond of MEA itself and cannot be observed in the spectrum. However, it can be seen from the 1557cm -1 、1605cm -1 The benzene ring skeleton vibration peak and 1700cm -1 The vibration peak of the aromatic aldehyde carbonyl group indirectly indicates that p-hydroxybenzaldehyde has been successfully grafted. Figure 1 It can be seen that the curves of the aldehyde-modified copolymer and gel elastomer have many burr-like peaks, which are also caused by the complex peak shape of the infrared spectrum of p-hydroxybenzaldehyde itself. The spectrum of the gel elastomer is basically consistent with the curve of the aldehyde-modified copolymer. This is because the content of the introduced imine is very low, with a cross-linking density of only 0.12%. At the same time, the stretching vibration characteristic peak of the generated imine bond is usually between 1690 and 1650 cm -1 , will also be covered up, but this reaction can be indirectly judged by the gelation phenomenon. The dissolution of the copolymer is essentially the free movement of its molecular chains under the action of solvation. When covalent cross-linking is introduced, the molecular chains will be restrained from moving each other after changing from a linear structure to a network structure, causing the solution to lose fluidity and gel. Therefore, if the reaction device is inverted, the imine-cross-linked gel elastomer will not flow downward, which can be used to judge the formation of imine cross-linking.
[0074] Depend on Figure 2 It can be seen that for Example 3, when the carboxyl groups of the terpolymer are replaced by p-hydroxybenzaldehyde esterification, the Tg is reduced from 2.3°C to -4.4°C because the polarity of the aldehyde group is significantly smaller than that of the carboxyl group; after further introduction of cross-linking, the linear molecular chain is transformed into a network structure, and the activity space of the molecular chain will be restrained by cross-linking again, resulting in a gradual increase in Tg from -4.4°C to 5.1°C.
[0075] At the same time, by Figure 2 It can be seen that the crosslinking density of Examples 1 to 3 gradually increases, the restriction on the molecular chain activity also increases accordingly, and Tg gradually increases; and the Tg of the gel elastomers of Examples 1, 2 and 3 are still lower than room temperature, ensuring that the gel elastomer still has chain motion-driven self-repair potential at room temperature or higher temperatures.
[0076] Depend on Figure 3 It can be seen that, for Example 3, the terpolymer has good thermal stability and starts to thermally decompose at about 322°C; however, the aldehyde copolymer and the gel elastomer are unstable, and the aldehyde copolymer starts to lose weight in advance. The starting temperature of the first weight loss stage is about 167°C, and it tends to be flat after 300°C. The mass loss in this stage is about 10%. The first stage decomposition temperature of the gel elastomers of Examples 1 to 3 is slightly higher than the decomposition temperature of the respective aldehyde copolymers, and the mass loss at the same temperature is also less, so the crosslinking effect slightly improves the stability of the product. In summary, the terpolymer, the aldehyde copolymer and the gel elastomer can ensure their thermal stability at least before 150°C.
[0077] At the same time, by Figure 3 It can be seen that for different cross-linking densities, the weight loss of the gel elastomers of Examples 1 to 3 is basically similar. Within a reasonable cross-linking density range, the gel elastomers with different cross-linking densities can maintain their thermal stability.
[0078] Comparative Example 1
[0079] 7.2 mL of MEA and 2.77 g of NIPAM were added to 32 ml of deionized water, and stirred vigorously in an ice bath for 10 min; then nitrogen was bubbled for 10 min to remove oxygen in the solution, and after continuing to stir in an ice bath for 5 min, 40 mg of AIBN was added, and polymerized under magnetic stirring at 30°C for 12 h to form a white gel copolymer product; the white gel copolymer product was taken out, and soaked in deionized water for 24 h, with the water changed every 8 h to remove unreacted monomers; then dried in a vacuum drying oven at 80°C; 5 g of the dried product was dissolved in 15 mL of acetone, the solution was injected into a mold and defoamed by a vacuum pump, and finally placed in the environment for natural volatilization to obtain the product.
[0080] Depend on Figure 4 and Figure 5 By comparison, it can be seen that the terpolymer of Example 3, compared with Comparative Example 1, introduces acrylic acid to provide grafting sites for the introduction of aldehyde groups in step 2, and its microphase separation degree is greatly reduced compared with Comparative Example 1. Figure 5 and Figure 6By comparison, it can be seen that after the terpolymer of Example 3 is further cross-linked to form a gel elastomer, the degree of microphase separation is slightly reduced, but the gel elastomer still maintains a relatively obvious microphase separation structure.
[0081] Depend on Figure 7 It can be seen that, compared with Comparative Example 1, after the terpolymer of Example 3 was copolymerized with 5% acrylic acid, its strain was greatly reduced from 1000% of Comparative Example 1 to 500% of step 1 of Example 3, and the stress was slightly reduced, and the modulus was greatly improved. It can also be seen that after the terpolymer of Example 3 was esterified in step 2, the carboxyl group of acrylic acid was converted into benzaldehyde, and the stress and modulus of the material were greatly weakened, which is consistent with the DSC glass transition temperature change law. However, when the cross-linking density was increased from 0.04% of Example 1, 0.08% of Example 2, and 0.12% of Example 3, the corresponding maximum stress and maximum strain showed a trend of gradual decline. This may be because the cross-linking density of 0.04mol% is already a relatively high value, and the cross-linking density is not the larger the better. Too large a cross-linking density leads to excessively tight molecular chains, which is not conducive to the uniform transfer of stress to the overall structure, resulting in local stress concentration and premature fracture.
[0082] Depend on Figure 8 and Fig. 9 It can be seen that the trends of the terpolymer and the gel elastomer are roughly the same. The terpolymer has a significantly larger displacement of the starting point of the five-cycle stretching than the gel elastomer, especially in the fourth and fifth cycles, the gel elastomer curve has better overlap, which further indicates that this tough cross-linking chemical action reduces the plastic deformation caused by interchain slippage and improves the material's resilience in repeated stretching. In addition, the terpolymer has a very large hysteresis in the first stretching than the gel elastomer, indicating that the material is accompanied by a large energy loss during the stretching process. The energy loss of the gel elastomer is calculated to be 1.7 of that of the terpolymer. This is mainly due to the fact that the dissociation of a large number of hydrogen bonds during stretching will absorb a large part of the energy, and after cross-linking, it will also be accompanied by the breaking of a small amount of imine bonds, and the imine bond energy is relatively large, which significantly increases the loss. In addition, the deformation recovery of the two after stretching can basically quickly recover to the original length after a period of time, especially after a certain temperature, and the material's slow elasticity is more significant.
[0083] Depend on Fig.10It can be seen that the self-healing performance of the gel elastomer of Example 3 is average at room temperature, and the scratches are only alleviated to a certain extent. However, when the temperature is raised to 75°C, the scars are significantly alleviated in just 1 hour, and the scars are difficult to observe after 8 hours, indicating that the gel elastomer of Example 3 has a good repair effect at a higher temperature. At the same time, the gel elastomer of Example 3 is completely cut off, and then the two cut gel elastomers are put together and repaired at 100°C for 8 hours to obtain the repaired sample. The repaired sample is then subjected to a load-bearing test. It can bear a large weight and remain unbroken for a long time. After the heavy object is removed, it can still slowly recover to its original length. It can be concluded that the repair performance of the gel elastomer has been greatly improved.
[0084] Depend on Fig.11 It can be seen that the self-healing effect of the gel elastomer of Example 3 increases with the increase of temperature. After 12 hours at 100°C, its stress is greatly repaired, with a stress recovery efficiency of up to 95%, the stress value recovering to 2.87 MPa, and the strain value recovering to 550%.
[0085] Depend on Fig.12 It can be seen that when the cross-linking density is 0.04 mol%, the gel elastomer has the largest initial stress value. At 1h and 4h, the self-repair stress recovery of the gel elastomer is low, less than 50% of the original sample, but the self-repair stress recovery is almost saturated after 8h. After 12h, the self-repair efficiency is about 80% and the stress value is about 2.5MPa, indicating that this cross-linking density may be better for the initial state of the material, but it is still not enough for self-repair.
[0086] Depend on Fig.13 It can be seen that when the cross-linking density is increased to 0.08 mol%, the density of imine on the self-healing interface has doubled, so more imine cross-links can be rebuilt to establish a stronger effect to offset the loss of chain movement and hydrogen bond self-repair. Therefore, at 1 hour, the stress recovery of the gel elastomer reached 50%. As the repair time gradually increased, the stress value gradually increased. At 12 hours, the stress increased to about 2.75 MPa. Combined with the initial stress slightly reduced due to the high cross-linking density, the calculated value of the repair efficiency reached 88%.
[0087] Depend on Fig.14 It can be seen that when the cross-linking density is increased to 0.12 mol%, the number of imines between the interfaces is no longer a bottleneck. When the repair time is 1 h, the stress recovery is about 60%; with the extension of time, the repair efficiency gradually increases. At 12 h, the stress repair is increased to 2.89 MPa, and the self-repair efficiency can be as high as 95%. In addition, at this cross-linking density, although the strain loss after repair is the highest, it is less than 10%.
[0088] Depend on Figure 12 to Figure 14 It can be seen that Example 1, Example 2 and Example 3 all follow the rule that the repair efficiency gradually increases with time. It is obvious that the repair of the cross section is not instantaneous, but a process of mutual penetration and re-action. The greater the cross-linking density and the more imine bonds, the better the self-healing effect. In summary, the gel elastomers of Examples 1 to 3 have excellent performance due to the improved mechanical strength and self-healing efficiency of imine cross-linking.
[0089] Example 4
[0090] (1) 9.3 mL of MEA, 0.92 g of NIPAM, 50 μL of AA and 40 mg of AIBN were fully dissolved in 32 mL of DMSO, and then nitrogen was bubbled for 10 min to completely eliminate oxygen in the reaction environment and the reaction system. The reaction vessel was then sealed with a rubber diaphragm, and polymerized under magnetic stirring at 70° C. for 12 h, and then quenched in an ice bath to obtain a viscous copolymer liquid; the viscous copolymer liquid was then extracted three times with methyl tert-butyl ether, and the extracted product was placed in deionized water for dialyzed purification, and finally dried in a drying oven at 80° C. to obtain a terpolymer;
[0091] (2) Same as step (2) of Example 3;
[0092] (3) Same as step (3) of Example 3.
[0093] Example 5
[0094] (1) 6.17 mL of MEA, 3.69 g of NIPAM, 50 μL of AA and 40 mg of AIBN were fully dissolved in 32 mL of DMSO, and then nitrogen was bubbled for 10 min to completely eliminate oxygen in the reaction environment and the reaction system, and then the reaction container was sealed with a rubber diaphragm; polymerization was carried out under magnetic stirring at 70°C for 12 h, and then quenched in an ice bath to obtain a viscous copolymer liquid; the viscous copolymer liquid was extracted three times with methyl tert-butyl ether, and the extracted product was placed in deionized water for dialyzed purification, and finally dried in a drying oven at 80°C to obtain a terpolymer;
[0095] (2) Same as step (2) of Example 3;
[0096] (3) Same as step (3) of Example 3.
[0097] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for preparing a high-strength self-repairing gel elastomer, characterized in that: The method comprises the following steps: Step 1, dissolving MEA, NIPAM, AA and initiator in a sufficient or excessive amount of solvent, and then polymerizing in a sealed oxygen-free environment for 8 to 16 hours; then cooling the temperature to stop the polymerization reaction, so that the active intermediate becomes a stable compound, and a viscous copolymer liquid is obtained; then the viscous copolymer liquid is extracted with an ether liquid to remove unreacted small molecules, and then the extracted product is placed in a purification agent for dialysis purification to remove the solvent and the ether liquid, and after drying to remove the purification agent, a terpolymer is obtained; The molar ratio of MEA, NIPAM, AA and initiator is (40-95):(5-60):(1-10):(1-5); Step 2, dissolving the terpolymer in a sufficient or excessive amount of solvent to form a homogeneous system; then adding p-hydroxybenzaldehyde, DMAP and DCC, and performing an esterification reaction at room temperature for 20 to 28 hours; then centrifuging the solution after the reaction; placing the separated supernatant in a dialysis bag, and then placing the dialysis bag in a purification agent for dialysis purification to remove unreacted small molecules and solvents, and drying to remove the purification agent to obtain an aldehyde-modified copolymer; The mass ratio of the terpolymer, p-hydroxybenzaldehyde, DMAP and DCC is (400-500):(20-40):(2-4):(45-60); Step 3, stirring and dissolving the aldehyde-modified copolymer in a sufficient or excessive amount of solvent to obtain a aldehyde-modified copolymer solution; dissolving the polyetheramine in the solvent as a cross-linking stock solution; then stirring the cross-linking stock solution and the aldehyde-modified copolymer solution at room temperature until they are uniformly mixed, vacuum degassing, placing at a temperature of 30 to 50° C. for cross-linking and gelation, and drying to remove the solvent to obtain a gel elastomer; The mass ratio of the solvent in the aldehyde copolymer solution to the solvent in the cross-linking stock solution is 300-500:
1.
2. The method for preparing a high-strength self-repairing gel elastomer according to claim 1, characterized in that: In step 1, the initiator is azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, potassium persulfate, ammonium persulfate or sodium persulfate; and the reaction temperature of the polymerization reaction is 60-90°C.
3. The method for preparing a high-strength self-repairing gel elastomer according to claim 1, characterized in that: In step 1, the number of extractions is 2 to 5 times; the specific process of each extraction is: firstly, the ether liquid and the viscous copolymer liquid are mixed uniformly by shaking, and then the separation is accelerated by centrifugation; The ether liquid uses methyl tert-butyl ether; The dialysis purification time is 18~30h, and the purification agent is replaced every 6~8h; deionized water is used as the purification agent.
4. The method for preparing a high-strength self-repairing gel elastomer according to claim 1, characterized in that: In step 2, the concentration of the terpolymer in the homogeneous system is 200-300 mg / mL; the dialysis purification time is 18-30 hours, and the purification agent is replaced every 6-10 hours; and deionized water is used as the purification agent.
5. The method for preparing a high-strength self-repairing gel elastomer according to claim 1, characterized in that: In step 2, the molecular weight cutoff of the dialysis bag ensures that the reaction product cannot enter or exit the dialysis bag, while the solvent and the purification agent can enter or exit the dialysis bag; the molecular weight cutoff of the dialysis bag is 3000-20000.
6. The method for preparing a high-strength self-repairing gel elastomer according to claim 1, characterized in that: In step 3, the time for cross-linking, gelation and drying is 3 to 10 hours; and the cross-linking density is 0.01 to 0.3 mol%.
7. The method for preparing a high-strength self-repairing gel elastomer according to claim 1, characterized in that: In step 1 to step 3, the solvent is anhydrous ethanol, dimethyl sulfoxide, N,N-dimethylformamide, acetone or dichloromethane.
Citation Information
Patent Citations
Method for synthesizing temperature-sensitive and biodegradable in situ gel
CN101845120A
Preparation method of acylhydrazone-bond-based dynamic reversible self-repair magnetic field / temperature-responsive intelligent hydrogel
CN105713134A
Dual-network hydrogel with high-toughness, shape-memory and self-repairing characteristics and preparation method of dual-network hydrogel
CN108727610A
Method for preparing flexible electronic device with high conductivity, self repairing and stretchability
CN108877996A
Self-repairing polyacrylate elastomer with multi-phase structure and preparation method thereof
CN112831007A
